Targeted Genetic Reduction of Mutant Huntingtin Lessens Cardiac Pathology in the BACHD Mouse Model of Huntington's Disease - Park, Saemi; Luk, Shu Hon Christopher; Bains, Raj S.; Whittaker, Daniel S.; Chiem, Emily; Jordan, Maria C.; Roos, Kenneth P.; Ghiani, Cristina A.; Colwell, Christopher S. (Frontiers in Cardiovascular Medicine, 2021)
Individuals affected by Huntington's disease (HD) present with progressive degeneration that results in a wide range of symptoms, including cardiovascular (CV) dysfunction. The huntingtin gene (HTT) and its product are ubiquitously expressed, hence, the cardiomyopathy could also be driven by defects caused by its mutated form (mHTT) in the cardiomyocytes themselves. In the present study, we sought to determine the contribution of the mHTT expressed in the cardiomyocytes to CV symptoms. We utilized the BACHD mouse model, which exhibits many of the HD core symptoms, including CV dysfunction. This model allows the targeted genetic reduction of mHTT expression in the cardiomyocytes while maintaining the expression of the mHTT in the rest of the body. The BACHD line was crossed with a line of mice in which the expression of Cre recombinase is driven by the cardiac-specific alpha myosin-heavy chain (Myh6) promoter. The offspring of this cross (BMYO mice) exhibited a dramatic reduction in mHTT in the heart but not in the striatum. The BMYO mice were evaluated at 6 months old, as at this age, the BACHD line displays a strong CV phenotype. Echocardiogram measurements found improvement in the ejection fraction in the BMYO line compared to the BACHD, while hypertrophy was observed in both mutant lines. Next, we examined the expression of genes known to be upregulated during pathological cardiac hypertrophy. As measured by qPCR, the BMYO hearts exhibited significantly less expression of collagen1a as well as Gata4, and brain natriuretic peptide compared to the BACHD. Fibrosis in the hearts assessed by Masson's trichrome stain and the protein levels of fibronectin were reduced in the BMYO hearts compared to BACHD. Finally, we examined the performance of the mice on CV-sensitive motor tasks. Both the overall activity levels and grip strength were improved in the BMYO mice. Therefore, we conclude that the reduction of mHtt expression in the heart benefits CV function in the BACHD model, and suggest that cardiomyopathy should be considered in the treatment strategies for HD.